Pregnancy Rates to Artificial Insemination in Yearling Beef Heifers Is Not Influenced by Injectable Trace Mineral - S. K. Johnson; M. W. Holman (Kansas Agricultural Experiment Station Research Reports, 2016)
Heifers that conceive early in their first breeding season have a long-term advantage in future reproductive success and production. Reproductive performance is more likely to be maximized if nutritional requirements are met, including those for trace minerals. Reproductive response to supplementation of trace minerals has been variable. Bioavailability of source, mineral antagonisms, intake, and long-term animal nutrient status may all contribute to that variability. A recent study found pre- and post-partum bolus injections of trace mineral increased pregnancy rate to AI in mature beef cows. The objective of this study was to determine the impact of an injectable trace mineral supplement on pregnancy rates to AI in developing replacement heifers.
Keywords: Beef Cattle Research